Analysis Of The Cognitive Content Of Two Types Of Swimming According To Content Organization Indicators And Their Impact On Technical Performance And Achievement - Muhammad Suhail Najm Al-Hamdani; Doaa Subhan Mahmoud Al-Zuhairi (Indonesian Journal of Physical Education and Sport Science)
Study purpose. University curricula need continuous review, analysis, change, and development due to their strong association with methodological variables. The analysis of the scientific material for swimming (the textbook) according to the indicators of organizing the educational content for swimming activities should be followed to identify the shortcomings and strengths and then follow up on modern educational directives. The study aims to reveal the degree of inclusion of indicators of organizing the educational content for swimming events. Also, it seeks to select and organize proposed educational content for the freestyle and breaststroke swimming events.